Evaluasi Pengendalian Sistem Informasi Penjualan Pada PT. XYZ - Husni, Hari Setiabudi; Tandra, Tan Willy; Anugrah, Ade (Bina Nusantara University, 2010)
The objective of this research is to evaluate sales information system that is ongoing in PT XYZ and to identify problems in sales system and also to recommend a renovation suggestion towards sales application so it goes well, accurate, and high-quality. The research method in this paper is including important data and information collecting, literature study and field research: observation, interview and questionnaire. The result is identified that sales information system controlling in PT XYZ still needs development especially in upgrading system and recruitment in IT division to supervise application system to avoid potential risks that will influence targeting company objective.